2021
DOI: 10.1111/jvh.13595
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiota in hepatitis B disease progression and treatment

Abstract: Current therapeutic interventions can only suppress hepatitis B virus (HBV) replication or reduce complications without a cure. Therefore, further development of new treatment methods is critical for the global eradication of HBV. Accumulating evidence suggests that the liver and gut share an interconnected relationship referred to as the 'Gut-Liver Axis', where exchanges happen bi-directionally. The gut itself is the host to a unique microbiota profile which has metabolic, immunological, neurological and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 72 publications
(189 reference statements)
0
12
0
Order By: Relevance
“…The results of this study showed that the patients' AST, TG, TC, and ALT improved more significantly when they were treated with hepatoprotective therapy and the observation group was treated with antiviral therapy alone. Although the basic hepatoprotective therapy could improve liver function, fibrosis level, and ballooning changes to some extent, the effect was more significant with the addition of the antiviral method, and the patients were able to achieve 89% and 100% of the liver function level and HBV DNA conversion rate after the treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the patients' AST, TG, TC, and ALT improved more significantly when they were treated with hepatoprotective therapy and the observation group was treated with antiviral therapy alone. Although the basic hepatoprotective therapy could improve liver function, fibrosis level, and ballooning changes to some extent, the effect was more significant with the addition of the antiviral method, and the patients were able to achieve 89% and 100% of the liver function level and HBV DNA conversion rate after the treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ammonia concentration was 96 (87.25-117.75), whereas the level declined to 74 (70-82) at week 20 post-FMT in the case series by Mehta et al [ 25 ]. From the same study, a statistically significant reduction in liver parameters such as the Child-Turcotte-Pugh score (from 9.5 [9-10.75] to 8 [ 7 - 8 ]) and MELD score (from 18 [16.25-19] to 15 [ 14 - 16 ]) was also observed [ 25 ]. Therefore, the evidence suggests that FMT may be beneficial in hindering the progression of chronic liver disease.…”
Section: Reviewmentioning
confidence: 92%
“…On the other hand, it is hypothesized that factors often seen in chronic liver diseases (CLD), such as portal hypertension and immunological dysfunction, can disrupt the microbiome and lead to complications, such as translocation of bacteria and bacteria-derived byproducts, which can further worsen the liver injury, fibrosis, and systemic inflammation [ 2 , 3 ]. On a molecular level, sinusoidal cells in fibrotic livers produce less nitric oxide, a vasoactive agent, than in non-fibrotic livers [ 7 , 8 ]. Consequently, it can precipitate higher portal pressure that can lead to worsening of portal hypertension and subsequently to further complications, such as variceal bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers discovered that Neisseriaceae positively correlated with serum levels of hepatitis B viral DNA, and the oral microbiota dysbiosis during hepatitis B infection was associated with a yellow coating of the tongue, indicating a decrease in Bacteroidetes but an increase in Proteobacteria. 16…”
Section: Role Of Gut Microbiota In Liver Diseasementioning
confidence: 99%